Effect of chronic prenatal exposure to the food additive titanium dioxide E171 on respiratory activity in newborn mice - Colnot, Eloïse; O’Reilly, Julie; Morin, Didier (Frontiers in Pediatrics, 2024)
Nanoparticles (NPs) possess unique properties that make their use valuable in all industries. Titanium dioxide (TiO2) NPs are extensively used as a white pigment in food (labeled under the European number E171) and personal care products, which creates a significant potential for chronic consumer exposure. Concerns about the potential toxic effects of TiO2 NPs have arisen, particularly in vulnerable populations, including pregnant women and infants. Recently, human materno-fetal transfer of E171 was demonstrated, and simultaneously, we reported that chronic prenatal exposure to reference P25 TiO2 NPs was found to alter the developing respiratory neural networks. In this study, using whole body plethysmography from postnatal day (P) 0 to P7, we assessed the respiratory function of newborn mice born to mothers fed with E171 during pregnancy. We also evaluated the potential alterations to respiratory centers by using brainstem-spinal cord electrophysiological recordings from P0 to P6. Our study reveals that E171-prenatally exposed animals displayed an abnormally elevated breathing rate from P3 onwards. From P5 to P6, the respiratory-related burst frequency generated by the isolated brainstem-spinal cord preparations was significantly higher in E171-exposed animals than in nonexposed animals. These findings demonstrate prenatal toxicity of E171 to the developing respiratory function and may contribute to policy-making regarding the use of TiO2 NPs.